Latissimus dorsi muscle free flap for management of large complex wound - Baiz Abdlrahman Miran, Abdlrahman (Zanco Journal of Medical Sciences (ZJMS), 2023)
Background and objective: Dealing with a large complex wound is very challenging, and latissimus dorsi flap through history has been used as its very variable and flexible in the form of pedicle or free flap in the coverage of those large complex wounds as its large, well perfused, and flexible in configuration. The study aimed to evaluate the versatility of use and viability of latissimus dorsi free flap for coverage of large complex wounds in different parts of the body. Methods: A retrospective study was conducted from 2012 to 2019 in Erbil Rizgary teaching hospital, Rozhawa emergency hospital, and PAR private hospital, Kurdistan region, Iraq on 22 cases, (20) male (90.9%), and (2) female (9.1%), all with a large complex wound in different sites of the body that latissimus dorsi free flap in the form of myocutaneous mainly and only one with muscle free flap. Results: The complex large wounds ranged from (22*15 cm – 35*20 cm) indifferent sites of the body, (18) from the lower limb,(3) from the forearm and (1) from the scalp, from those 22 cases, we had 17 cases that survived totally(77.2%), and 5 failure cases (22.7%) those were from leg who associated with tibial bone fracture gestilo type 111B and C and large soft tissue defect with or without vascular injury, and in regard to flaps out of 22 cases 5 of them presented with total necrosis (55.6%), one case with partial necrosis(11.1%), and 3 cases with partial skin graft loss (33.33%), that managed conservatively, in all cases donor site closed primarily with few morbidities as happened in 5 cases (22.7%) like bleeding in 3 cases (60.0%) and stoppage needed operation theater, one case (20.0%) with seroma, and one with minor wound dehiscent (20.0%), that both managed conservatively. Conclusion: The latissimus dorsi myocutaneous free flap is the reliable, flexible and highly recommended for large soft tissue defect reconstruction in different sites of the body especially those associated with extensive bone damage.